Separation of superparamagnetic particles through ratcheted Brownian motion and periodically switching magnetic fields - Liu, Fan (Biomicrofluidics, 2016)
Brownian ratchet based particle separation systems for application in lab on chip devices have drawn interest and are subject to ongoing theoretical and experimental investigations. We demonstrate a compact microfluidic particle separation chip, which implements an extended on-off Brownian ratchet scheme that actively separates and sorts particles using periodically switching magnetic fields, asymmetric sawtooth channel sidewalls, and Brownian motion. The microfluidic chip was made with Polydimethylsiloxane (PDMS) soft lithography of SU-8 molds, which in turn was fabricated using Proton Beam Writing. After bonding of the PDMS chip to a glass substrate through surface activation by oxygen plasma treatment, embedded electromagnets were cofabricated by the injection of InSn metal into electrode channels. This fabrication process enables rapid production of high resolution and high aspect ratio features, which results in parallel electrodes accurately aligned with respect to the separation channel. The PDMS devices were tested with mixtures of 1.51 μm, 2.47 μm, and 2.60 μm superparamagnetic particles suspended in water. Experimental results show that the current device design has potential for separating particles with a size difference around 130 nm. Based on the promising results, we will be working towards extending this design for the separation of cells or biomolecules.